Extracellular Mitochondrial‐Derived Vesicles Affect the Progression of Diabetic Foot Ulcer by Regulating Oxidative Stress and Mitochondrial Dysfunction - Huihui Zhang; Zi Yan; Junyou Zhu; Ziyue Li; Lianglong Chen; Weihan Zheng; Zhenning Dai; Jiaxin Yang; Xinyi Yun; Yilin Wang; Hai Zhou; Ziwei Jiang; et al. (Advanced Science)
Abstract Diabetic foot ulcer (DFU) is a common and severe complication of diabetes mellitus, the etiology of which remains insufficiently understood, particularly regarding the involvement of extracellular vesicles (EVs). In this study, nanoflow cytometry to detect EVs in DFU skin tissues is used and found a significant increase in the Translocase of Outer Mitochondrial Membrane 20 (TOM20)+ mitochondrial‐derived vesicles (MDVs). The role of MDVs in DFU is yet to be reported. Using single‐cell datasets, it is discovered that the increase in MDVs may be regulated by Sorting Nexin 9 (SNX9). In vitro experiments revealed that MDVs secreted by fibroblasts cultured in high glucose medium exhibited similar composition and protein enrichment results to those in DFU tissues, suggesting their potential as an ideal in vitro surrogate. These MDVs promoted apoptosis and intracellular oxidative stress, disrupted mitochondrial structure, and reduced aerobic metabolism in target cells. In vivo experiments also showed that MDV drops hindered wound healing in diabetic mice; however, this effect is rescued by SNX9 inhibitors, restoring mitochondrial dynamics and balance. Under high glucose conditions, MDVs significantly upregulated oxidative stress levels and induced mitochondrial dysfunction. This study proposes targeting MDVs as a potential therapeutic strategy for DFU.